2016
DOI: 10.1186/s12864-016-3032-4
|View full text |Cite
|
Sign up to set email alerts
|

Small RNA and degradome profiling reveals miRNA regulation in the seed germination of ancient eudicot Nelumbo nucifera

Abstract: BackgroundMicroRNAs (miRNAs) play important roles in plant growth and development. MiRNAs and their targets have been widely studied in model plants, but limited knowledge is available concerning this small RNA population and their targets in sacred lotus (Nelumbo nucifera Gaertn.).ResultsIn this study, a total of 145 known miRNAs belonging to 47 families and 78 novel miRNAs were identified during seed germination using high-throughput small RNA sequencing. Furthermore, some miRNA families which have not yet b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 61 publications
1
27
0
Order By: Relevance
“…The length of unique sRNAs, in both the N816S and Ning5m libraries, the 24 nt category was most abundant (average of 59.15% and 62.90% in N816S and Ning5m libraries, respectively) (Figure 2C-D). This is consistent with the typical lengths of plant sRNAs reported in other studies(Asha et al, 2016;Hu et al, 2016).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The length of unique sRNAs, in both the N816S and Ning5m libraries, the 24 nt category was most abundant (average of 59.15% and 62.90% in N816S and Ning5m libraries, respectively) (Figure 2C-D). This is consistent with the typical lengths of plant sRNAs reported in other studies(Asha et al, 2016;Hu et al, 2016).…”
Section: Resultssupporting
confidence: 93%
“…However, few studies on the relationships between miRNA biogenesis and CMS occurrence during anther development in pepper were very limited. MiRNAome and degradation sequencing technology provides an effective way to identify and evaluate the expression profiles of miRNAs and targets associated with CMS occurrence in plant tissues during anther development(Wei et al, 2015;Hu et al, 2016;Bai et al, 2017). To explore the roles of miRNAs during the occurrence of CMS, anthers at the early uninucleate stage were used to examine the expression profiles of the miRNAs in the sterile line N816S and its maintainer line Ning5m using high-throughput sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…To confirm targets of the miRNAs experimentally, a degradome (SRX1598165) of germinating lotus seedlings was analyzed (Hu et al, 2016). The raw reads were first cleaned by removing low-quality nucleotide reads and adapters using NGS QC Toolkit (v2.3.3) (Patel and Jain, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Although the population and abundance of miRNAs in lotus have been explored (Zheng et al, 2013; Hu et al, 2016; Pan et al, 2016; Shi et al, 2016), there are no reports on systematic identification and characterization of submergence-related miRNAs in lotus. In this study we determined the submergence response of miRNAs in lotus.…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are small, endogenous, noncoding RNAs ranging from 19 to 24 nucleotides that play crucial regulatory roles at the post-transcriptional stage by cleavage or translation repression of their target mRNAs (Bartel 2004). Increasing evidence suggests that miRNA-guided gene regulation is involved in multiple physiological and biochemical processes, such as seedling growth (Hu 2016), floral development (Chen 2004), male and female sterility (Millar 2005 andYan 2015), and responses to environmental stress (Sunkar 2007). Furthermore, a new study has found that plants can export miRNAs to inhibit virulence gene expression in a fungal pathogen (Zhang 2016).Thus, identifying miRNAs and their target mRNAs is essential to elucidating their regulatory mechanisms, and to understand the growth, development, and stress response processes.…”
Section: Introductionmentioning
confidence: 99%